EXHIBITION REVIEWS. Issue 3 (1st September 2013) - Byers, Catherine; Cecil, Anne
'LOUIS VUITTON – MARC JACOBS', LES ARTS DÉCORATIFS, PARIS, 9 MARCH–16 SEPTEMBER 2012WHO TAKES THE PICTURES? AN EXHIBIT REVIEW OF CINDY SHERMAN, MUSEUM OF MODERN ART, 2012